Framing Analysis of News Reporting on Sugar Commodity Corruption Case by Kompas.com - Triwanto, Rio Bayu; AÔÇÖyun, Ariza Qurrota; Lani, Oktri Permata; Avrilian, Pepy (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
frames the alleged corruption case of sugar imports involving Thomas Trikasih Lembong, the former Minister of Trade. Using the social reality construction approach and Robert Entman's framing model, this study found that Kompas.com tends to frame the news by emphasizing Tom Lembong's direct involvement as a suspect, even though the substance of the news content is relatively uniform. This framing not only influences public perception but also creates a narrative that can direct readers' opinions. This finding shows the important role of the media in shaping social reality and its consequences for the legal process and political stability. This seems to be one of Kompas.com's strategies to support the increase in the electability of the attorney general's office which has recently appeared on social media in handling various corruption cases.